Advanced information systems engineering : 29th International Conference, CAiSE 2017, Essen, Germany, June 12-16, 2017, Proceedings /: 29th International Conference, CAiSE 2017, Essen, Germany, June 12-16, 2017, Proceedings. (2017) - Unknown
No abstract available